Current Situation and Development About Quantitative Study of Needling Techniques - 刘堂义 杨华元 蒯乐 高明 黄国琪（翻译） (Journal of acupuncture and tuina science, 2008)
In the review of the literature on the quantitative study of the needling techniques, the authors believe that modern scientific technology plays an important role in the quantitative study of the needling techniques, submit the research methods and channels of the quantitative study of the needling techniques under the current condition, foresee its development prospects and emphasize the significance of the quantitative study of the needling technique in the teaching, clinical service and research process of acupuncture.